Latihan yoga terhadap berat badan, persen lemak tubuh, dan lingkar perut pada wanita dewasa overweight - Putri Nur Fatimah; Fillah Fithra Dieny; Etisa Adi Murbawani; Ahmed Fahmy Arif Tsani (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Obesity caused diabetes and cardiovascular disease. Yoga considered three aspects, physic, emotion and mental that helped in obesity therapy.Objective: This research aimed to explain the influence of yoga excercise on body weight, percent of body fat, waist circumference and waist to hip ratio (WHR) in overweight women.Method: This research applied quasi experiment design by using pre-post test with control group design. The subjects of research were 31 women aged 19-25 years old and divided into 2 groups, treatment group and control group. Treatment group was prepared to do yoga in 60 minutes for 10 times during 20 days and given nutrition education, whereas control group was given nutrition education only. Data body weight and percentage of body fat were measured by bioimpedance analysis; waist circumference and WHR were measured by tape measures; food intake were assessed by food recall and food frequency questionnaire. Data were analyzed using paired t-test and independent t-test.Results: There was a significant difference of body weight before and after intervention in both groups. The body weight on treatment group decreased by 0.81 ± 1.29 kg (p<0.05), while the body weight on the control group increased. Percentage of body fat and waist circumference decreased on both of groups, however treatment group decreased more than the control group. WHR no significant on both of groups. Yoga excercise resulted no significant influences on body weight, percentage of body fat, waist circumference and WHR in overweight women (p>0.05). Conclusion: Obesity women with 10 times yoga had no significant influences on body weight, percentage of body fat, waist circumference and WHR.